Health education about COVID-19 pandemic through Youtube Channel Community Pharmacy News - Lucia Hendriati; Galuh Nawang Pramesti; Ida Ayu Andri; Diga Albrian; Teguh Widodo (University of Merdeka Malang, 2022)
To meet information related to the COVID-19 pandemic, people usually search the internet, most of this is YouTube, which is the dominant source finding information. The purpose of this community service was to provide valid information in terms of pharmaceutical science, easy to understand by the public regarding the prevention and treatment of COVID-19 so that people can behave appropriately. The method was carried out by providing audiovisual information related to the COVID-19 pandemic through the “Pharmacy Community News” YouTube channel. The evaluation was measured by the number of viewers and the number of comments on the video. Educational videos made by students of the Faculty of Pharmacy UKWMS based on research journals under the guidance of lecturers. The information presented includes the themes: hand sanitizers and disinfectants; hoaxes related to COVID-19; vitamins and herbal as immunomodulators; guidelines of COVID-19 treatment and others related to COVID-19. For a year, these videos have been viewed 18,969 times and received 1490 times comments as responses from the public. Based on this data, we can conclude that health education related to COVID-19 during the pandemic through the Youtube channel can reach the wider community and can provide the valid information.